Upregulation of XIAP promotes lung adenocarcinoma brain metastasis by modulating ceRNA network - Wang, Yingjing; Shen, Lu; Li, Geng; Chen, Jiayi; Ge, Rong (Frontiers in Oncology, 2022)
Dysregulation of XIAP has been shown to affect the progression of a variety of cancers, including lung adenocarcinoma (LUAD). However, the function and mechanisms of XIAP in lung adenocarcinoma with brain metastasis (LUAD-BM) remains poorly understood. In this study, we analyzed the differential mRNA of 58 lung adenocarcinomas samples and 28 lung adenocarcinomas with brain metastases in GEO database. 191 differentially expressed mRNAs were significantly associated with immune response, the proliferation of the immune cell, cell-cell adhesion. Subsequent analyzed by lasso and SVM found that XIAP was significantly elevated in LUAD-BM and significantly associated with LUAD grade and metastasis. Then we constructed a molecular regulatory network of ncRNA-miRNA-mRNA ceRNA by Cystoscope based on the correlation obtained from Starbase. It was found that SBF2-AS1 or RUNDC3A-AS1, has-miR-338-3p and XIAP may have a regulatory relationship. Furthermore, we also initially found that XIAP was closely correlation with T cells, B cells, Mast cells, macrophages, and dendritic cells. In conclusion, we found that XIAP was significantly higher expressed in LUAD-BM compared with LUAD without brain metastasis, suggesting that XIAP may play an important role in the future prediction and clinical treatment of LUAD-BM.